Course of Encephalopathy in a Cirrhotic Dialysis Patient Treated Sequentially with Peritoneal and Hemodialysis - Suleyman Koz; Idris Sahin; Zafer Terzi; Sema Tulay Koz (Case Reports in Medicine)
End-stage kidney disease and advanced cirrhosis are sometimes seen concomitantly. There is no consensus on dialysis modality in terms of determining the optimal way of treating these patients. It has been suggested that peritoneal dialysis is a better choice for these patients, but efficacy of hemodialysis in stable cirrhotic patients has not been evaluated sufficiently. We report a case with advanced cirrhosis and end-stage kidney disease who was faced with hepatic encephalopathy episodes up on starting renal replacement therapy. The case is also interesting in that it reveals effects of hemodialysis and peritoneal dialysis on hepatic encephalopathy episodes and quality of life of the patient.